Aktivitas Psikostimulan Tanaman Bajakah (Spatholobus suberectus) : Studi In Silico Terhadap Protein 4M48-Dopamine Transporter - Priyadi, Muhammad; Saputra, Rizki Rachmad; Gunawan, Yohanes Edy; Citrariana, Shesanthi; Decenly, Decenly; Febrianto, Yahya (Jurnal Farmasi & Sains Indonesia, 2023)
Bajakah plants (Spatholobus suberectus) have been widely used by Dayak tribes in Kalimantan with various properties that are believed and have also been studied for various tests of phytochemical compound content and pharmacological tests. Secondary metabolite compounds from bajakah (Spatholobus suberectus) have potential as psychostimulant compounds. The purpose of this study was to investigate the psychostimulant activity of bajakah plants (Spatholobus suberectus) through analysis of the interaction between bajakah secondary metabolite compounds and the 4M48-Dopamine Transporter receptor (PDB: 4M48), which is one of the dopamine transporter proteins. Ligand and receptor interactions were analyzed using molecular docking method with Autodock Vina 4 application with nortriptyline compound as native ligand and 15 secondary metabolite compounds for testing. The results of docking analysis showed that the standard ligand nortriptyline compound has an affinity value of -10.2 kcal/mol. There are 3 compounds from bajakah that have affinity values close to the standard compounds plathymenin, butein and eriodictyol with affinity values of -9.7 kcal/mol, -9.4 kcal/mol and -9.2 kcal/mol respectively. Based on the analysis conducted, it can be concluded that bajakah plants (Spatholobus suberectus) have the potential to be developed as psychostimulant therapy.